In-silico Evaluation of the effects of blood flow rate change in ductus arteriosus on cardiac function and cerebral blood flow rate in term and preterm infants - Bozkurt, Surhan; Bal, Ridvan; Ayten, Umut Engin (ELSEVIER SCI LTD, 2024)
The transition of cardiovascular system is vital for newborn infants. It is expected that ductus arteriosus which is vessel between aorta and pulmonary arteries closes in the first day of life. However, ductus arteriosus may not close within 24 h in preterm infants. In this study, a lumped parameter model was used to evaluate the effects of the change in blood flow rate through ductus arteriosus on cardiac function and cerebral blood flow rate in term and preterm neonatal infants. Mean arterial pressure increased from 41 mmHg to 53 mmHg at 24th hour after birth in term neonatal infant cardiovascular system model whereas it increased from 33 mmHg to 43 mmHg in preterm neonatal infant cardiovascular system model. Left cardiac output decreased from 911 mL/min to 721 mL/min and right cardiac output increased 551 mL/min to 706 mL/min in term neonatal infant cardiovascular system model. Left cardiac output decreased from 705 mL/min to 612 mL/min and right cardiac output increased 369 mL/min to 484 mL/min in preterm neonatal infant cardiovascular system model. Cerebral blood flow rate increased from 115 mL/min to 147.40 mL/min in term neonatal infant cardiovascular system model at 24th hour after birth and it increased 29.65 mL/min to 38.92 mL/min in preterm neonatal cardiovascular system model. The results showed that blood flow rate through ductus arteriosus alters cardiac function and cerebral blood flow rate in both term and preterm cardiovascular system models.
Keywords: Neonatal infant cardiovascular system model; Cardiac function; Cerebral blood flow rate; ECHOCARDIOGRAPHIC MEASUREMENTS; TRANSITION; HEMODYNAMICS; CIRCULATION; PRESSURE; VELOCITY; MODEL; Engineering